The nucleotide sequence of the putative transcription initiation site of a cloned ribosomal RNA gene of the mouse. - Urano, Y (1980)
Approximately one kilobase pairs surrounding and upstream the transcription initiation site of a cloned ribosomal DNA (rDNA) of the mouse were sequenced. The putative transcription initiation site was determined by two independent methods: one nuclease S1 protection and the other reverse transcriptase elongation mapping using isolated 45S ribosomal RNA precursor (45S RNA) and appropriate restriction fragments of rDNA. Both methods gave an identical result; 45S RNA had a structure starting from ACTCTTAG---. Characteristically, mouse rDNA had many T clusters (greater than or equal to 5) upstream the initiation site, the longest being 21 consecutive T's. A pentadecanucleotide, TGCCTCCCGAGTGCA, appeared twice within 260 nucleotides upstream the putative initiation site. No such characteristic sequences were found downstream this site. Little similarity was found in the upstream of the transcription initiation site between the mouse, Xenopus laevis and Saccharomyces cerevisiae rDNA.